Spatially-resolved relation between [C i] 3P1–3P0 and 12CO (1–0) in Arp 220. (16th March 2022) - Ueda, Junko; Michiyama, Tomonari; Iono, Daisuke; Miyamoto, Yusuke; Saito, Toshiki
Abstract: We present $\sim {0.^{′ ′ }3}$ (114 pc) resolution maps of [C i ] 3 P 1 – 3 P 0 (hereafter [C i ] (1–0)) and 12 CO (1–0) obtained toward Arp 220 with the Atacama Large Millimeter/submillimeter Array. The overall distribution of the [C i ] (1–0) emission is consistent with the CO (1–0). While the [C i ] (1–0) and CO (1–0) luminosities of the system follow the empirical linear relation for the unresolved ULIRG sample, we find a sublinear relation between [C i ] (1–0) and CO (1–0) using the spatially-resolved data. We measure the [C i ] (1–0)$/$ CO (1–0) luminosity ratio per pixel in star-forming environments of Arp 220 and investigate its dependence on the CO (3–2)$/$ CO (1–0) ratio ( R CO ). On average, the [C i ] (1–0)$/$ CO (1–0) luminosity ratio is almost constant up to R CO ≃ 1 and then increases with R CO . According to the radiative transfer analysis, a high C i $/$ CO abundance ratio is required in regions with high [C i ] (1–0)$/$ CO (1–0) luminosity ratios and R CO > 1, suggesting that the C i $/$ CO abundance ratio varies at ∼100 pc scale in Arp 220. The [C i ] (1–0)$/$ CO (1–0) luminosity ratio depends on multiple factors and may not be straightforward to interpret. We also find the high-velocity components traced by [C i ] (1–0) in the western nucleus, likely associated with the molecular outflow. The [C i ] (1–0)$/$ CO (1–0) luminosity ratio in the putative outflow is 0.87 ± 0.28, which is four times higher than the average ratio of Arp 220. While there is a possibility that the [C i ] (1–0) and CO (1–0) emission traces different components, we suggest that the high line ratios are likely to be because of elevated C i $/$ CO abundance ratios based on our radiative transfer analysis. A C i -rich and CO-poor gas phase in outflows could be caused by the irradiation of the cosmic rays, the shock heating, and the intense radiation field.